추운 사람의 따뜻한 사람 선호: 사회적 배제가 따뜻한 색과 연합된 사람 선호에 미치는 효과 - 이국희; Lee, Guk-Hee (인지과학, 2018)
Previous works have observed that persons who have experienced social exclusion have lower perceptions of body temperature and environmental temperature, and seek physical warmth such as warm drinks and warm water shower. The present study aimed to expand the results of these previous works to the dimensions of color emotions or color symbols. Hence, four experiments were conducted in which pictures of people with warm or cold colors applied to them were shown to the subjects, who were asked to evaluate the people in the pictures to determine whether their preferences changed depending on their perception of social exclusion. The results showed that the subjects with perceived social exclusion had stronger preferences for people in warm colors over those in cold colors, but the subjects without perceived social exclusion had no differences in their preferences for the people in the two types of colors. This study is significant in that it expanded the compensation hypothesis, which states that people try to compensate their psychological loss by pursuing external goals from the physical dimension to the emotional and symbolic dimensions. Furthermore, this study has implications in that it proposes the need for warm emotions in places where people who have experienced social exclusion are treated, such as psychological counseling centers. 선행연구들은 사회적 배제를 경험한 사람은 체온과 환경온도 지각이 낮아지고, 이를 보충하기 위해 따뜻한 음료나 따뜻한 물 샤워 같은 물리적 따뜻함을 추구함을 관찰해왔다. 본 연구는 이러한 선행연구의 결과를 색 감성 혹은 색 상징의 차원으로 확장하기 위한 목적에서 이루어졌다. 이를 위해 사람들에게 따뜻한 색 혹은 차가운 색을 입힌 인물 사진을 보여준 후, 해당 인물에 대한 호감을 평가하게 할 때, 사회적 배제 지각에 따라 호감이 달라지는지 네 가지 실험을 통해 확인하였다. 결과적으로 사회적 배제를 지각한 사람은 따뜻한 색과 연합된 인물에 대한 호감이 차가운 색과 연합된 인물에 대한 호감보다 강했지만, 사회적 배제를 지각하지 않은 사람들은 두 색에 연합된 인물에 대한 호감에 차이가 없었다. 본 연구는 심리적 손실을 외적 목표 추구를 통해 상쇄하려 한다는 보충가설을 물리적 차원에서 감성적, 상징적 차원으로 확장했다는 측면에서 중요하다. 또한 심리상담소와 같은 사회적 배제를 경험한 사람들을 치료하는 현장에 따뜻한 감성이 필요함을 제안한다는 측면에서도 시사점을 가진다.